Electroacupuncture treatment can improve cognitive impairment in spontaneously hypertensive rats: a preliminary DTI study - Liu, Ji-peng; Han, Bing-xuan; Liu, Yu; Nie, Bin-bin; Bian, Tao; Liu, Chuan; Xia, Tian-qi; Gong, Yu; Tu, Long-teng; Zhang, Jing; Wang, Bing-hui; Yang, Yi; et al. (Frontiers in Neuroscience, 2025)
BackgroundHypertension is a significant risk factor for cognitive impairment. Our group’s previous rs-fMRI study has found that acupuncture can enhance the functional connectivity of brain regions related to cognitive function, thereby protecting the cognitive function of spontaneously hypertensive rats (SHRs).MethodsThis study aimed to reveal the effects of electroacupuncture on the white matter structure in the brain regions of SHRs using the diffusion tensor imaging (DTI) technique. 20 SHRs were divided into the electroacupuncture group (EA) and the model group (SHR), and 10 Wistar-Kyoto rats were established as the normal control group (WKY). Electroacupuncture was applied to Taichong (LR3) and Zusanli (ST36) acupoints for 12 weeks, with treatment every other day. Blood pressure was measured once every 2 weeks, with DTI scans and the Morris water maze (MWM) tests performed at the end of the 12-week electroacupuncture intervention.ResultsThe results showed that electroacupuncture significantly decreased systolic and diastolic blood pressure and enhanced spatial learning and memory in SHRs. DTI analysis revealed that hypertension led to increased axial diffusivity (AD), mean diffusivity (MD), and radial diffusivity (RD) values in brain regions such as the hippocampus, prefrontal cortex, striatum, amygdaloid body, posterior lobe of cerebellum, olfactory bulb, and piriform cortex, indicating white matter microstructural damage. Electroacupuncture improved these injuries, especially significantly improving the integrity of the hippocampal white matter structure. Correlation analysis showed that hippocampal white matter structure parameters were significantly correlated with behavioral manifestations of MWM.ConclusionTherefore, we speculate that electroacupuncture can alleviate white matter damage in the hippocampus, prefrontal cortex, striatum, and other brain regions, thereby preventing cognitive impairment in SHRs, which may be one of the reasons for the efficacy of electroacupuncture.